Xanthan gum: Secondary raw materials for biosynthesis, isolation and application - G. F. Kurbanov; A. O. Prichepa; N. Yu. Sharova (Пищевые системы)
The inevitable consequence of population growth is the development of agriculture and food production, which in turn has an impact on the volumes of secondary raw materials production. The processing of these materials can present significant challenges. One of the most effective solutions to this problem is the use of microbiological synthesis to create products with high added value. A notable example is xanthan gum, a biopolymer that has been utilized in a multitude of industries, including food, oil, pharmaceutical, and medicine. The value of xanthan gum is contingent upon its distinctive physicochemical properties, particularly its capacity to enhance the viscosity of solutions. The process of obtaining xanthan gum is conducted through the fermentation of liquid high-carbon media. The primary producer is the bacterium Xanthomonas campestris, a phytopathogen of cruciferous plants, which converts carbohydrates into a biopolymer of commercial value. This literature review examines several topics related to xanthan gum and its synthesis by X. campestris, with particular attention paid to the success of obtaining the target product using food production waste and secondary agricultural raw materials.